2006
DOI: 10.1007/s10482-005-9043-9
|View full text |Cite
|
Sign up to set email alerts
|

Halomonas maura is a physiologically versatile bacterium of both ecological and biotechnological interest

Abstract: Halomonas maura is a bacterium of great metabolic versatility. We summarise in this work some of the properties that make it a very interesting microorganism both from an ecological and biotechnological point of view. It plays an active role in the nitrogen cycle, is capable of anaerobic respiration in the presence of nitrate and has recently been identified as a diazotrophic bacterium. Of equal interest is mauran, the exopolysaccharide produced by H. maura, which contributes to the formation of biofilms and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 72 publications
(71 reference statements)
1
42
0
Order By: Relevance
“…Halomonas maura does not differ from this model, particularly in that EPS is essential to its formation of biofilms (Arco et al, 2005;Llamas et al, 2006). As mentioned above, the GacS/ GacA TCS controls EPS biosynthesis in H. anticariensis, which prompted us to investigate whether this system affects biofilm formation.…”
Section: Discussionmentioning
confidence: 95%
“…Halomonas maura does not differ from this model, particularly in that EPS is essential to its formation of biofilms (Arco et al, 2005;Llamas et al, 2006). As mentioned above, the GacS/ GacA TCS controls EPS biosynthesis in H. anticariensis, which prompted us to investigate whether this system affects biofilm formation.…”
Section: Discussionmentioning
confidence: 95%
“…are usually associated with aerobic environments and have subsequently been used in several biotransformation studies under aerobic conditions, including the degradation of catechol (Alva and Peyton 2003) and salicylate (Oie et al 2007). However, some Halomonas spp., including H. maura, are capable of anoxic respiration under nitrate reducing conditions (Aragandoña et al 2006;Llamas et al 2006;Peyton et al 2001). Previous studies have utilized Halomonas isolates to study metal-microbe interactions under anoxic conditions (Francis et al 2000;Khijniak et al 2003), although Cr(VI) reduction by a Halomonas isolate has not been reported.…”
Section: Resultsmentioning
confidence: 99%
“…in the sandstone column environment may be related to the known ability of these organisms to form biofilms (e.g., Klausen et al, 2006; Li et al, 2009) thus giving them a competitive advantage in sessile environments. Halomonas sp., also enriched in the sandstone columns (Table 1), are also known biofilm and exopolysaccharide-forming organisms that may allow for the solubilization of hydrocarbons attached to rock (Llamas et al, 2006; Qurashi and Sabri, 2012; Gutierrez et al, 2013). Members of this genus have also been found to be associated with oil reservoirs and the deep biosphere (Mnif et al, 2009; Dong et al, 2013).…”
Section: Discussionmentioning
confidence: 99%